Joint modeling of tumor dynamics and progression‐free survival in advanced breast cancer: Leveraging data from amcenestrant early phase I-II trials - Marc Cerou; Hoai‐Thu Thai; Laure Deyme; Sophie Fliscounakis‐Huynh; Emmanuelle Comets; Patrick Cohen; Sylvaine Cartot‐Cotton; Christine Veyrat‐Follet (Wiley, 2024)
Abstract A joint modeling framework was developed using data from 75 patients of early amcenestrant phase I-II AMEERA‐1‐2 dose escalation and expansion cohorts. A semi‐mechanistic tumor growth inhibition (TGI) model was developed. It accounts for the dynamics of sensitive and resistant tumor cells, an exposure‐driven effect on tumor proliferation of sensitive cells, and a delay in the initiation of treatment effect to describe the time course of target lesion tumor size (TS) data. Individual treatment exposure overtime was introduced in the model using concentrations predicted by a population pharmacokinetic model of amcenestrant. This joint modeling framework integrated complex RECISTv1.1 criteria information, linked TS metrics to progression‐free survival (PFS), and was externally evaluated using the randomized phase II trial AMEERA‐3. We demonstrated that the instantaneous rate of change in TS (TS slope) was an important predictor of PFS and the developed joint model was able to predict well the PFS of amcenestrant phase II monotherapy trial using only early phase I-II data. This provides a good modeling and simulation tool to inform early development decisions.